ANALISIS KONSTRUKSI SOSIAL: PENENTUAN SEKOLAH PADA ANAK USIA DINI OLEH ORANG TUA MILENIAL DI KECAMATAN KARTASURA - Dina Wanda Purnama; Bagas Narendra Parahita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Examining the phenomenon of growing private school enrollment compared to public schools, this study seeks to uncover the reasons millennial parents in Kartasura District select particular schools for their children. Peter L. Berger's social construction theory provides the framework for understanding these choices. Berger's perspective suggests that social reality, rather than being objective, is formed through a dialectical process involving externalization, objectification, and internalization. Applied to educational selection, this means that millennial parents socially construct their perceptions of